Analisis Hasil Karya Seni Lukis Menggunakan Bahan Cat Poster Pada Siswa Kelas XI SMA Negeri 1 Purbatua Tahun Ajaran 2020/2021 Ditinjau Dari Prinsip-Prinsip Seni Rupa - Jhoni Sailendra Saragih; Nelson Tarigan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the quality of the work of class XI students of SMA Negeri 1 Purbatua for the 2020/2021 academic year in painting four-legged animals by applying the principles of fine art using poster paint materials. The method used in this research is descriptive qualitative and qualitative data analysis techniques collected using observation and documentation. The results of this study indicate that the results of painting four-legged animals by class XI students of SMA Negeri 1 Purbatua on average get a good category. Category A has 1 work (2%), category B has 39 works (73.5%), and category C has 13 works (24.5%). The proportion indicator gets category B with a total average of 3.01, the composition assessment aspect gets category B with a total average of 3.32, the gradation indicator gets category B with a total average of 3.12, the balance indicator gets category B with a total average 3.33 average, and finishing indicators get category B with a total average of 3.21. Thus, the lack of work by class XI students of SMA Negeri 1 Purbatua lies in the proportion indicator. In conclusion, the students' work was good and the students' ability to master the plaque technique was good. It is recommended that students study and practice more in the practice of painting using poster paint materials with the plaque technique, especially in the application of fine art principles.